Altitude: Acclimatization to intermediate altitudes
At intermediate altitudes, 1,500-3,000 meters, up to 25% of unacclimatized travelers may experience AMS (acute mountain sickness). People with serious lung, heart and blood diseases are more likely to develop AMS. Healthy young adults who participate in vigorous activity upon arrival at altitude are also at great risk for AMS. Individuals with a prior history of AMS and who live at low elevations are especially susceptible.Those who travel rapidly to altitude, as is common with air travel, are also at greater risk for AMS.